Enhancing nursing education through e-portfolios: evaluating the impact on learning effectiveness, self-efficacy, and job satisfaction of NPGY trainees - Fang-Chun Wei; Li-Ju Kao; Chia-Ting Chang; Jui-Yuan Chung (BMC Medical Education)
Abstract Background Traditionally, learning was documented using paper-based systems, leading to challenges in tracking and evaluating progress. Electronic portfolios (e-portfolios), offering digital documentation and real-time feedback, have become increasingly popular in clinical education. This study aims to assess the impact of e-portfolios on the learning effectiveness, self-efficacy, and job satisfaction of nursing postgraduate year (NPGY) trainees. Methods A cross-sectional questionnaire survey was conducted among 114 NPGY trainees in a medical center in northern Taiwan. The questionnaire collected data on demographics, e-portfolio satisfaction, assessment tool satisfaction, technology acceptance model (TAM), learning effectiveness, self-efficacy, and job satisfaction. Statistical analyses, including t-tests, ANOVA, and Pearson correlation, were performed to evaluate the relationships between variables. Results Satisfaction with e-portfolios, assessment tools, and TAM significantly impacted learning effectiveness (p < .001), self-efficacy (p < .001), and job satisfaction (p < .001). The self-efficacy of trainees in the 1–2 years stage was higher than those in the 0–3 months stage (p < .05). Although the job satisfaction score was lowest during the 4–12 months stage, the difference was not statistically significant, indicating a need for targeted interventions during this period. Conclusions E-portfolios positively influence the learning outcomes and job satisfaction of NPGY trainees. Continuous usage and enhancement of e-portfolios are recommended to meet user needs and provide a supportive learning environment, especially during critical stages of training. Future research should explore strategies to optimize e-portfolio features to further improve professional development and satisfaction.